Lipid Nanoparticle-Mediated Liver-Specific Gene Therapy for Hemophilia B - Brijesh Lohchania; Porkizhi Arjunan; Gokulnath Mahalingam; Abinaya Dandapani; Pankaj Taneja; Srujan Marepally (MDPI AG, 2024)
Background/Objectives: Hemophilia B is a hereditary bleeding disorder due to the production of liver malfunctional factor IX (FIX). Gene therapy with viral vectors offers a cure. However, applications are limited due to pre-existing antibodies, eligibility for children under 12 years of age, hepatotoxicity, and excessive costs. Lipid nanoparticles are a potential alternative owing to their biocompatibility, scalability, and non-immunogenicity. However, their therapeutic applications are still elusive due to the poor transfection efficiencies in delivering plasmid DNA into primary cells and target organs in vivo. To develop efficient liver-targeted lipid nanoparticles, we explored galactosylated lipids to target asialoglycoprotein receptors (ASGPRs) abundantly expressed on hepatocytes. Methods: We developed 12 novel liposomal formulations varying the galactose lipid Gal-LNC 5, cationic lipid MeOH16, DOPE, and cholesterol. We evaluated their physicochemical properties, toxicity profiles, and transfection efficiencies in hepatic cell lines. Among the formulations, Gal-LNC 5 could efficiently transfect the reporter plasmid eGFP in hepatic cell lines and specifically distribute into the liver in vivo. Toward developing functional factor IX, we cloned Padua mutant FIX-L in a CpG-free backbone to enhance the expression and duration. Results: We demonstrated superior expression of FIX with our galactosylated lipid nanoparticle system. Conclusions: The current research presents a specialized lipid nanoparticle system viz. Gal-LNC which is a specialized lipid nanoparticle system for liver-targeted gene therapy in hemophilia B patients that has potential for clinical use. The Gal-LNC successfully delivers a CpG-free Padua FIX gene to liver cells, producing therapeutically relevant levels of FIX protein. Among its benefits are the ideal qualities of stability, targeting the liver specifically, and maximizing efficiency of transfection. Optimization of liver-targeting lipid nanoparticle systems and function FIX plasmids will pave the way for novel lipid nanoparticle-based gene therapy products for hemophilia B and other monogenic liver disorders.